Non-Destructive Oil Palm Fresh Fruit Bunch (FFB) Grading Technique Using Optical Sensor - Utom, Sebastian Liban; Mohamad, Elmy Johana; Abdul Rahim, Ruzairi; Yeop, Noorfarahane; Mohmad Ameran, Hanis Liyana; Abdul Kadir, Herdawatie; Mohd Muji, Siti Zarina; Pusppanathan, Jaysuman (International Journal of Integrated Engineering, 2018)
This research discover the uniqueness of physical and optical characteristics of the oil palm Fresh Fruit Bunches (FFB). The goal is to determine the level of ripeness of the oil palm FFB by creating a non-destructive and real-time oil palm FFB grading systems. This grading system are a solution to automate the current grading process in order to provide more accurate and reliable results. Apart from that, the costs, labor and time consume will also be reduced. In Malaysia, the grading of oil palm FFB are still performed manually by observing the surface color as the main quality attribute. This project explore the chlorophyll content in oil palm and use its characteristic as a level selector to classify the degree of oil palm FFB ripeness. In this case, the level of ripeness are divided into three categories which is unripe, ripe and over-ripe. There are several phases involve in the non-destructive oil palm FFB grading system using optical sensor. First phase is the determination of reflectance data for all three classes of the oil palm FFB. This will be determine by using a light sources with 670 nm wavelength. The light sources will emitted a projection of light that will illuminate the skin of the oil palm FFB. The reflected light will be received by the optical sensor and the reflectance value are obtain. Last phase is the analysis of the data obtained by using statistical analysis. The expected outcome of this project is to study and understand the process of using LED and optical sensor as the data collecting method to determine the level of ripeness of the oil palm FFB.